2012
DOI: 10.1038/nbt.2355
|View full text |Cite
|
Sign up to set email alerts
|

RNA processing enables predictable programming of gene expression

Abstract: Complex interactions among genetic components often result in variable systemic performance in designed multigene systems. Using the bacterial clustered regularly interspaced short palindromic repeat (CRISPR) pathway we develop a synthetic RNA-processing platform, and show that efficient and specific cleavage of precursor mRNA enables reliable and predictable regulation of multigene operons. Physical separation of linked genetic elements by CRISPR-mediated cleavage is an effective strategy to achieve assembly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
177
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 191 publications
(183 citation statements)
references
References 34 publications
3
177
0
Order By: Relevance
“…Highly expressed constructs might impair the growth rate and decrease steady-state dilution of cellular contents, which would lead to an overestimation of transcription and translation strengths. We analyze only promoter and RBS pairings here, but future studies can test large numbers of any composable genetic designs to assess their effectiveness on a broad basis (26,28).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Highly expressed constructs might impair the growth rate and decrease steady-state dilution of cellular contents, which would lead to an overestimation of transcription and translation strengths. We analyze only promoter and RBS pairings here, but future studies can test large numbers of any composable genetic designs to assess their effectiveness on a broad basis (26,28).…”
Section: Discussionmentioning
confidence: 99%
“…Current efforts have focused on approaches to limit the number of time-consuming steps required to characterize potential interactions and on identifying existing or engineered elements that act predictably when used in combination (26)(27)(28). However, these studies still suggest there are enough idiosyncratic interactions and context effects that it will be necessary to construct and measure many variants of a circuit to achieve desired function (29).…”
mentioning
confidence: 99%
“…However, the two functional elements might interfere with each other by the promoter escaping process (38) or by the formation of some structures inaccessible to ribosomes on the messenger RNA. Different insulators have been reported to eliminate the unanticipated regulatory element interaction in E. coli (33,39). Here, we introduced the well-elucidated RiboJ insulator between promoter and RBS to improve the predictability of the combination.…”
Section: The Riboj Insulator Enables Predictable Combination Of Promomentioning
confidence: 99%
“…This can be obtained by inserting either a rybozyme or a CRISPR target sequence between the 5' UTR sequence and the ribosome binding site [17,18,19]. Testing of constructs with di↵erent UTR sequences demonstrated that insertion of a CRISPR target sequence substantially reduces variability in protein production rate [18]. Similarly, employment of rybozymes in NOT gates showed robustness to the genetic context [17].…”
Section: Modularity Of Basic Partsmentioning
confidence: 99%
“…To decouple the properties of the promoter from those of the ribosome binding site, the 5' UTR sequence can be physically separated from the ribosome binding site to avoid unpredictable interference between these two. This can be obtained by inserting either a rybozyme or a CRISPR target sequence between the 5' UTR sequence and the ribosome binding site [17,18,19]. Testing of constructs with di↵erent UTR sequences demonstrated that insertion of a CRISPR target sequence substantially reduces variability in protein production rate [18].…”
Section: Modularity Of Basic Partsmentioning
confidence: 99%